2006
DOI: 10.2527/jas.2004-556
|View full text |Cite
|
Sign up to set email alerts
|

The response of gastrointestinal microbiota to avilamycin, butyrate, and plant extracts in early-weaned pigs1,2

Abstract: An experiment was designed to evaluate the effects of 3 different additives on the gastrointestinal microbiota of early-weaned pigs. Early-weaned (18 to 22 d; n = 32) pigs (6.0 +/- 0.10 kg of BW) from 8 litters were randomly distributed into 8 pens. Each pen was assigned 1 of 4 dietary treatments: a prestarter or control diet, the control diet with 0.04% avilamycin (AB), with 0.3% sodium butyrate, or with 0.03% plant extract mixture (XT; standardized mixture with 5% (wt/wt) carvacrol extracted from Origanum sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
98
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(111 citation statements)
references
References 30 publications
11
98
2
Order By: Relevance
“…The relationship between lactobacilli and enterobacteria populations has traditionally been considered as an index of desirable or undesirable bacteria in pigs, relating a high index with a greater resistance to intestinal disorders (165) . Adding butyrate to diets promoted greater mean values in this ratio (166) . Galfi & Bokori (140) observed changes in the ileal microbiota with a decrease in the proportion of coliform bacteria and a simultaneous increase of lactobacilli.…”
Section: Beneficial Effects On Performance and Intestinal Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between lactobacilli and enterobacteria populations has traditionally been considered as an index of desirable or undesirable bacteria in pigs, relating a high index with a greater resistance to intestinal disorders (165) . Adding butyrate to diets promoted greater mean values in this ratio (166) . Galfi & Bokori (140) observed changes in the ileal microbiota with a decrease in the proportion of coliform bacteria and a simultaneous increase of lactobacilli.…”
Section: Beneficial Effects On Performance and Intestinal Healthmentioning
confidence: 99%
“…Van Immerseel et al (167) , using microencapsulated butyrate in young chickens, also demonstrated a decrease in the caecum colonisation of Salmonella after an experimental infection. It was reported that oral butyrate supplementation would not influence the number of total bacteria inhabiting different sections of the GIT but rather promote the largest changes in the composition of the jejunal microbiota and in the ecological structure and metabolic activity of the microbial ecosystem of the large intestine (166) . These authors suggested that such changes in the upper GIT could potentially modify the fermentable material reaching the large intestine and, therefore, modify the microbial activity at the faecal level.…”
Section: Beneficial Effects On Performance and Intestinal Healthmentioning
confidence: 99%
“…The composition of the gut microbiota can change dramatically in response to changes in diet; however, these changes do not always happen quickly. It can take several weeks for activators of microbial degradation enzymes, such as xylanase and cellulose, to adjust to a new diet (Castillo et al, 2006). In the case of omnivores and herbivores, the introduction of plant carbohydrates favors the growth of species that are adapted to the fermentation of dietary fiber.…”
Section: Effect Of Dietmentioning
confidence: 99%
“…According to Castillo et al (2006) the aldehyde carvacrol present in cinnamon improves the growth of lactobacilli, thus increasing the share of useful intestinal microflora. Furthermore garlic supplementation improved feed conversion ratio, body weight, carcass characteristics, as well as survivability in poultry (Javed et al, 2009;Kumar et al, 2010;Mohebbifar and Torki, 2011).…”
Section: Growth Performance and Feed Consumptionmentioning
confidence: 99%